а)
=============================================
б)
в)
1)х^2-25=x^2-5^2=(x+5)*(x-5)
2)4х^2 - 6х^3= 2x^2*(2-3x)
3) х^2 + 2х -3=х^2 + 2х -2-1=(x^2-1)+(2x-2)= (x+1)(x-1)+2(x-1)=(x-1)(x+3)
а)![x^{2}-25=(x)^{2}-(5)^{2}=(x-5)(x+5)](/tpl/images/0039/2866/d41b2.png)
=============================================
б)![4x^{2}-6x^{3}=2x^{2}(2-3x)](/tpl/images/0039/2866/61d8c.png)
=============================================
в)![x^{2}+2x-3=x^{2}+(3x-x)-3=(x^{2}-x)+(3x-3)=x(x-1)+3(x-1)=(x-1)(x+3)](/tpl/images/0039/2866/21816.png)
1)х^2-25=x^2-5^2=(x+5)*(x-5)
2)4х^2 - 6х^3= 2x^2*(2-3x)
3) х^2 + 2х -3=х^2 + 2х -2-1=(x^2-1)+(2x-2)= (x+1)(x-1)+2(x-1)=(x-1)(x+3)